Navigating E-Government Realities: Insights from Rural Administration in Central Maluku, Indonesia: Melintasi Realitas E-Government: Wawasan dari Administrasi Desa di Maluku Tengah, Indonesia - Rolobessy, Mike J; Soasio, Sukur; Rukoyah (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative and descriptive study delves into the implementation of E-Government in Banda Subdistrict, Central Maluku, Indonesia. Utilizing purposive sampling, data was gathered through field observations, documentation, and interviews. The research aims to comprehend the significance of E-Government in Banda Subdistrict, evaluating the benefits, challenges, stages, and strategies involved in its implementation. Emphasis is placed on the observation that despite the presence of websites in many villages, only a few remain active and visited by the community. Success in E-Government for village administrative services is influenced by factors such as technological infrastructure, community understanding of technology, and the readiness of human resources. This study underscores the need for a comprehensive approach to address these factors, enhancing the effectiveness of E-Government initiatives in rural areas. Highlights: Strategic Evaluation: Assessing the benefits, challenges, and implementation strategies of E-Government in Banda Subdistrict provides insights into its overall effectiveness. Community-Centric Approach: Highlighting the importance of community engagement, the study underscores that successful E-Government relies on the understanding and active participation of the local population. Technological Foundations: Emphasizing the role of technology infrastructure, the research identifies it as a critical factor influencing the success of E-Government initiatives, particularly in rural administrative settings. Keywords: E-Government, Rural Administration, Technology Infrastructure, Community Engagement, Implementation Strategies